PENGUATAN PERUBAHAN PERILAKU DALAM PERCEPATAN PENURUNAN STUNTING - Siti Nurhidayah; Hasan Basri; Ridwan Ridwan; Irlan Suarlan (An-Nizam, 2022)
The implementation of community service carried out in Karawang Regency related to strengthening behavior change in accelerating stunting reduction is carried out with three activities, namely holding stunting prevention is important, stunting prevention socialization through bilingual pamphlets and outreach to pregnant women. The service implementation applies the community education method in the form of socialization. Community service is carried out within a month with locations in three hamlets, namely Kaliasin 2 Hamlet, Karang Mulya Hamlet and East Junta Hamlet. The results of the implementation of the service show that parents, especially mothers and prospective mothers, know and understand ways and steps to prevent and minimize stunting, increase community enthusiasm to maintain a healthy lifestyle as well as good parenting, increase awareness to participate in stunting programs and know how to prevent delays growth of toddlers, preventing children from being susceptible to infectious diseases, preventing poor performance in their learning focus and memory abilities.